1992
DOI: 10.1159/000200875
|View full text |Cite
|
Sign up to set email alerts
|

Soluble lnterleukin-2 Receptor, lnterleukin-6 and Interleukin-1 β in Patients with Crohn’s Disease and Ulcerative Colitis: Preoperative Levels and Postoperative Changes of Serum Concentrations

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) show an intestinal activation of T cells and macrophages within the inflamed lesions. The aim of the present prospective study was to determine whether circulating interleukins (IL) represent useful markers of immune activation in vivo and to characterize their respective roles in monitoring disease activity. Serum concentrations of the soluble IL-2 receptor (sIL-2R), IL-6 and IL-1 β were measured in 10 patients with CD and 10 patients with UC before, at day 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In this study we used resected intestinal tissue samples. It is conceivable that our identified cytokine differences may be demonstrable in tests on peripheral blood (12,25), thus permitting differentiation between the two clinical forms of CD using a blood test. Should our observations have therapeutic implications (see below), such peripheral blood testing would permit identification of those patients most likely to benefit from such therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used resected intestinal tissue samples. It is conceivable that our identified cytokine differences may be demonstrable in tests on peripheral blood (12,25), thus permitting differentiation between the two clinical forms of CD using a blood test. Should our observations have therapeutic implications (see below), such peripheral blood testing would permit identification of those patients most likely to benefit from such therapy.…”
Section: Discussionmentioning
confidence: 99%
“…All three cytokines share simi lar actions in vivo, i.e. induction of fever, wasting, leuko cytosis, and hepatic acute-phase protein synthesis, effects which are common features of flare-ups of IBD [34], In Crohn's disease serum IL-6 has been found elevated and it seems to reflect the degree of disease activity [35][36][37], Spontaneous or stimulated release of cytokines from blood monocytes has been found enhanced in Crohn's disease [38,39].…”
Section: Discussionmentioning
confidence: 99%
“… 6 In patients with IBD, increased serum concentrations of IL‐6 have been described 7–12 and its assessment may be useful as an indicator of disease activity and response to therapy. 8–10,12 Nevertheless, direct measurement of IL‐6 in the intestinal mucosa is more relevant to clarification of its involvement in the pathogenesis of IBD because alterations of serum IL‐6 concentrations may reflect complicated events, such as entry from the inflamed tissue into the intravascular space 7,13 and clearance from the circulation by the liver. 14 Recently, we and other investigators found that intestinal IL‐6 levels were elevated with an increased number of IL‐6‐producing cells in patients with active lesions of IBD.…”
Section: Introductionmentioning
confidence: 99%